CARDIAC MAGNETIC RESONANCE IMAGING IN DIFFERENTIAL DIAGNOSTICS OF ACUTE CORONARY SYNDROME IN PATIENTS WITH NON-OBSTRUCTION CORONARY ATHEROSCLEROSIS - V. V. Ryabov; S. B. Gomboeva; Т. A. Shelkovnikova; A. Е. Baev; М. S. Rebenkova; Yu. V. Rogovskaya; V. Yu. Usov (Российский кардиологический журнал)
Aim. To investigate on the nosological structure of acute coronary syndrome (ACS) in patients with non-obstruction coronary atherosclerosis (NOCA) before and after magnetic resonance imaging (MRI) of the heart.Material and methods. A non-randomized, open, controlled study (NCT02655718). The patients included, with ACS, older than 18 y.o., with NOCA (intact coronary arteries or stenosis ≤50%) confirmed by invasive coronary arteriography (ICAG). Patients with previous revascularization were not included.Results. In the year 2016, to emergency cardiology department (ECD) 913 ACS patients admitted. In 44 (4,8%) the NOCA was found. Mean age 54±10,4 y.o., males 68%, and the groups with ACS with ST elevation (STEACS) and none (NSTEANS) were comparable by clinical and anamnestic parameters. Intact coronary arteries were visualized in 16 (53%), non-significant coronary atherosclerosis was diagnosed in 14 (32%), slower coronary flow — 22 (73%). By MRI with contrast, performed in 11±8 days (2-43 days) from ACS beginning, myocardial oedema was found in 18 (41%), hyperemia in 13 (30%) and fibrosis in 40 (91%); there were no changes in 1 patient.Nosological structure of ACS in NOCA after MRI has been represented: by acute myocardial infarction (MI) in 24 (55%) cases, unstable angina (UA) — in 6 (14%), pseudocoronary myocarditis in 10 (23%), acute aorta dissection in 1 (2%), posttraumatic atherosclerosis in 1 (2%), congenital valve defect in 1 (2%), manifested Wolf-Parkinson-White (WPW) — in 1 (2%). In-hospital mortality was 2%. In comparison of ACS before and post MRI there was significant increase number of patients with myocarditis, by 20%.Conclusion. The prevalence of ACS in NOCA is 4,8%, that is comparable to literature data. Patients with ACS and NOCA are heterogenic group with MI, UA, myocarditis, acute aorta dissection, posttraumatic atherosclerosis, congenital defects, WPW syndrome. In-hospital mortality was 2%. Comparing the structure of the diagnoses before and after MRI, there was significant increase of myocarditis patients number. A high accuracy of MRI was found for differential diagnostics of ACS in NOCA, which was 78%.